Tri Hita Karana Based Yoga Model Instrument for Independent Student Exchange Students - I Wayan Muliarta (Universitas Pendidikan Ganesha, 2024)
Implementing the Tri Hita Karana concept in character and spiritual values education in higher education significantly impacts students' holistic well-being. However, developing assessment instruments for implementing this concept is still lacking. This research aims to develop a Tri Hita Karana-based yoga model instrument for Merdeka exchange students. This type of research is development research using the ADDIE method. The subjects of this research were 2 learning content experts, 2 language experts, and 2 learning design experts. The trial subjects were 30 independent exchange students (3 in individual trials and 27 in small group trials). Data collection methods used include observation, interviews, and questionnaires. The instrument used in this research was a questionnaire sheet. The techniques used to analyze data are qualitative descriptive analysis and quantitative and inferential statistics. The research results, namely the assessments given by learning content experts, obtained an average score of 94.5%, resulting in very good qualifications. The assessment results given by language experts were 93% (very good qualifications). The assessment results given by learning design experts were 96.5% (very good qualifications). The results of the practicality test given by the lecturer received an average score of 96% (very practical). The results of the individual trial assessment were 92% and small group trials 95%, so getting a very practical qualification. The t-test results show a difference in the average value of holistic well-being among students after using the Tri Hita Karana Based Yoga Model Instrument. It was concluded that the Tri Hita Karana Based Yoga Model Instrument is feasible and effective to use to improve the holistic well-being of independent exchange students.